2015 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2015
DOI: 10.1109/iros.2015.7353736
|View full text |Cite
|
Sign up to set email alerts
|

Real-time needle steering in response to rolling vein deformation by a 9-DOF image-guided autonomous venipuncture robot

Abstract: Venipuncture is the most common invasive medical procedure performed in the United States and the number one cause of hospital injury. Failure rates are particularly high in pediatric and elderly patients, whose veins tend to deform, move, or roll as the needle is introduced. To improve venipuncture accuracy in challenging patient populations, we have developed a portable device that autonomously servos a needle into a suitable vein under image guidance. The device operates in real time, combining near-infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
(16 reference statements)
0
27
0
Order By: Relevance
“…Based on his results and the study by Romanelli & Falanga 120 , who measured skin induration on the leg with a hand-held type O durometer, Muthu found that a silicone material with a Shore A hardness of 20 displayed a similar force vs. needle tip displacement to that of cadaver skin for micro perforation. Chen et al 10 developed a computational model to simulate the mechanics of needle insertion into a blood vessel. Three situations that a practitioner might encounter during the puncture of a vein were simulated: a normal puncture when the axis of the needle matches the medial axis of the vein and a rolling or a rupture of the vein when the axes were not aligned to simulate patients with rolling or hardened veins.…”
Section: Tissue-mimicking Substitutes Related To Palpation and Surfacmentioning
confidence: 99%
“…Based on his results and the study by Romanelli & Falanga 120 , who measured skin induration on the leg with a hand-held type O durometer, Muthu found that a silicone material with a Shore A hardness of 20 displayed a similar force vs. needle tip displacement to that of cadaver skin for micro perforation. Chen et al 10 developed a computational model to simulate the mechanics of needle insertion into a blood vessel. Three situations that a practitioner might encounter during the puncture of a vein were simulated: a normal puncture when the axis of the needle matches the medial axis of the vein and a rolling or a rupture of the vein when the axes were not aligned to simulate patients with rolling or hardened veins.…”
Section: Tissue-mimicking Substitutes Related To Palpation and Surfacmentioning
confidence: 99%
“…Compared to manual cannulation, a robotic system may minimize errors due to misalignments between the needle and vessel, vessel rolling and deformation during insertion, and random arm motions. Previously, we described the mechanical design of a robotic venipuncture device [11,12] (Fig. 5a) and demonstrated early results in multilayered gelatin-based phantoms simulating the mechanical, optical, and ultrasonic properties of human skin, vessels, and blood [13].…”
Section: Resultsmentioning
confidence: 99%
“…The design of the current robot has been previously described in Refs. 25 and 26. These manuscripts also describe the cannulation process in detail and present vessel puncture success rates on tissue phantoms.…”
Section: Introductionmentioning
confidence: 99%